NILAI TAMBAH PELAKU BISNIS DI PELABUHAN PENDARATAN IKAN SODOHOA DALAM MENUNJANG PERTUMBUHAN EKONOMI KOTA KENDARI - Onu La Ola; Roslindah Daeng Siang; Nurdiana A . (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2016)
This study aimed to analyze the value added created by businesses (fisherman, the perpetrators of post-harvest/industrial, and traders) in TPI Sodohoa Kendari. The research method used a survey and Focus Group Discussion. The object of research are the amount of each type of capital goods production factors and working capital of actors of capture fisheries, industry and trade; The purchase price and the economic life of capital goods; Types of fish that are produced; Amound of production; and The price of buying and selling fish at TPI Sodohoa. The results obtained are massive creation of value added by the use or final demand the perpetrators of production activities and transactions fishery commodities in TPI Sodohoa Kendari city 2015 amounted Rp199.410.000.000,-Keywords : Fishing, Industry, Traders, Value Added